Javanese Culture in Maternal Postpartum Care at Hargomulyo Village, Kedewan District, Bojonegoro Regency - Devi Endah Saraswati (Universitas Nahdlatul Ulama Surabaya, 2021)
Maternal and child health problems are inseparable from socio-cultural and environmental factors in society. Factors of belief and traditional knowledge positively or negatively impact Maternal and Child Health (MCH). Culture could be a predisposing factor for high maternal mortality. This paper describes Javanese culture in maternal postpartum care at Hargomulyo Village, Kedewan District, Bojonegoro Regency. This study was descriptive research. It took place at Hargomulyo Village, Kedewan District, Bojonegoro Regency, from January to February 2020. The population was mothers who have experienced postpartum both primipara and multipara. There were 48 respondents by total sampling. The instrument used a questionnaire consisting of several questions regarding culture in maternal postpartum care, how to carry out the culture, and its reasons. Thirty respondents did food taboos (62.5%), six respondents limited their drinking water (12.5%), 40 respondents drank herbs (83.3%), 47 respondents wore stagen (97.9%), and five respondents used pilis (10.4%). In addition, 48 respondents performed brokohan and mendem ari ari (100%), 20 respondents were not allowed to take a nap (41.7%), and 18 respondents must be at home for 40 days (37.5%). At the same time, 17 respondents did perineal care after birth with betel leaf (35.4%), 12 respondents walked and sat with feet parallel (25%), and 20 respondents did semi-sitting position (41.7%). Postpartum mothers still practice many Javanese cultures. This culture has both favorable and unfavorable impacts on health. Furthermore, it is necessary to analyze the influence of Javanese culture on the health status of postpartum mothers.